The Correlation of Family Knowledge about Hypertension with Family Support for Stroke Patients at General Hospital Haji Medan - Tapiheru, Jasmine Aulia Putri; Sari, Mila Trisna (Universitas Muhammadiyah Sumatera Utara, 2024)
Abstract: Hypertension is called a silent killer because it does not show symptoms when high blood pressure continues for a long period so it will cause complications such as stroke. Stroke can cause disability and death so it becomes a serious problem for families and patients. Family support is an important aspect of patient treatment and can help the patient's recovery and treatment. This research aims to analyses the relationship between family knowledge about hypertension and family support in stroke patients at the General Haji HospitalMedan. This study is a descriptive study with a cross-sectional design to determine the level of knowledge about hypertension and family support in stroke patients. This study uses a bivariate test using the Spearman Rho test. The results of this research bivariate test with the Spearman Rho test showed a correlation between family knowledge of patients regarding hypertension and family support in stroke patients (r value 0.001 a = 0.05) with a correlation coefficient of 0.763. It can be concluded that family knowledge is significant and strongly with family support which indicates a relationship between family knowledge about hypertension and good family support in stroke patients at the General Haji Hospital Medan.